Innowacje w administracji publicznej - Ewa Krok (Studia i Materiały)
The article defines the concept of innovation in public organizations and classifies innovation due to different criteria. The author presents the obstacles in raising the innovation of public administration and finally makes the proposals for improvement actions. Analyses show that it is advisable to focus on design thinking and co-creation, it means active participation of citizens in public life, shaping the attitudes and proinnovation behavior among staff offices, as well as activities related to technology, such as improving the accessibility and quality of public e-services, improving the efficiency of digital office, data integration, and first of all to increase the availability and usage of public sector information, which is to ensure wide access to data.